A Visualization of Teaching the Indirect Method for Computing Cash from Operations - SEOW, Poh Sun (Institutional Knowledge at Singapore Management University, 2011)
The Statement of Cash Flows (SCF) complements the Statement of Financial Position and the Statement of Comprehensive Income by explaining where the cash came from (cash receipts) and how the cash was spent (cash payments) (Harrison Jr. et al. 2011; Powers and Needles Jr. 2010). International Accounting Standard (IAS) 7 requires companies to classify cash flows during the accounting period according to operating, investing and financing activities (International Accounting Standards Board 2010). IAS 7 also requires companies to report net cash flows from operating activities using either the direct method or the indirect method (International Accounting Standards Board 2010). Most companies adopt the indirect method in preparing the net cash flows from operating activities section of SCF (American Institute of Certified Public Accountants 2010; Harrison Jr. et al. 2011; Powers and Needles Jr. 2010; Romeo and Bao 2011). The American Institute of Certified Public Accountants conducted a survey and found that 99 per cent of respondents use the indirect method (American Institute of Certified Public Accountants 2010). As the indirect method is predominantly used by companies, it is important to ensure that students understand the indirect method of preparing SCF. This paper presents a visualization method to teach the indirect method in order to enhance the understanding of students.